Korelasi Pola Makan dan Status Sosial Ekonomi dengan Kejadian Kegemukan pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Landasan Ulin - Sigit Yudistira; Norlisna Ariyanti; Nurul Hekmah; Norhasanah Norhasanah; Jidiwan Jidiwan; Rina Muliana; Nirmaya Nirmaya; Aulia Zahratun Nazwa (HB PRESS, 2025)
Obesity are characterized by a situation in which an individual's caloric intake exceeds caloric expenditure. It is widely recognized that factors contributing to obesity include diet and socio-economic status. Study aims investigate rapport between dietary patterns and socio-economic status with the incidence of obesity in toddler ages 24-59 months in the working area of The Landasan Ulin Health Center. This research employs an observational case-control design. A total sampling method with a 1:1 ratio was used, resulting in a sample size of 58 respondents each across case and control groups. Data on height were collected using microtoise, while dietary information and socio-economic status were gathered employ interviews and surveys. The chi-square test applied for analysis data. The results of this study show that the majority of respondents have a sufficient diet category, namely 70 people (60.3%) and the majority of respondents have a high economic status category, namely 72 people (62.1%). It can be concluded that dietary patterns (p=0.001) and socioeconomic status (p=0.002) are related to the incidence of obesity in toddlers aged 24-59 months in the Landasan Ulin Community Health Center Work Area. Recommended the parents allocate greater observance appropriate dietary patterns and physical activity that align with their child's needs.